Analyzing of ERP Utilization to Assess Production and Inventory Efficiency - Sunarko, Kusuma Melati Faizun; Sutarman, Sutarman (International Journal of Management and Business Applied, 2025)
This paper aims to assess production and inventory efficiency after the ERP system transition from Odoo to INSYS at PT. Mulia Cipta Rasa, a food manufacturing company in Indonesia, by applying lean manufacturing indicators. It further analyzes the obstacles encountered during the transition, how these obstacles affect production and inventory efficiency, and provides strategic recommendations for improvement.. Methodology/approach – This research used a qualitative descriptive method. Data were collected through interviews with relevant informant, supplemented by observations and internal company documentation. Analysis was conducted using lean manufacturing waste indicators.. Findings – It was found that. There is no increase in production and inventory efficiency after changing the INSYS ERP system, this is due to several obstacles such as inter-departmental dependencies, INSYS ERP system limitations, adaptation to different systems, lack of training and socialization, human error and employee resistance, mismatch between minimum purchase quantity (MOQ) and actual needs, not integrated with supplier systems that support real-time tracking. Novelty/value – While numerous studies have focused on ERP success factors, few have explored post-ERP system migration production and inventory efficiencies in the food manufacturing industry and the barriers affecting them. This paper offers contextual insights into ERP-related efficiencies and provides strategic direction specific to the dynamics of perishable goods production.